1985
DOI: 10.1159/000115805
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravenously Administered L-Acetylcarnitine on Somatosensory-Evoked Potentials

Abstract: The acute effects of intravenously administered L-acetylcarnitine (L-AC) were evaluated in 5 healthy and 20 diseased volunteers (17 vascular, 3 tumoral cerebral lesions). Short-latency scalp somatosensory-evoked potentials (SEPs) to simultaneous median, and separate unilateral peroneal nerve stimulation were carried out before and after L-AC administration (at 10-, 30- and 60-min intervals). L-AC did not influence peak and interpeak latencies; however, in a percentage of healthy and diseased volunteers a clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…importance of a measurement in vivo of the concentration of the muscarinic receptors, which are reduced in several clinical conditions like Alzheimer disease or Huntington disease is obvious. Rossini, Di Stefano et al [12] reported an increase in voltage of cortical SEPs following intravenous administrations of L-AC; the effect was evident 30' minute after drug administration, mostly on the affected hemisphere. SEP changes following thalamic and cortical lesions have been demonstrated in several studies.…”
mentioning
confidence: 98%
“…importance of a measurement in vivo of the concentration of the muscarinic receptors, which are reduced in several clinical conditions like Alzheimer disease or Huntington disease is obvious. Rossini, Di Stefano et al [12] reported an increase in voltage of cortical SEPs following intravenous administrations of L-AC; the effect was evident 30' minute after drug administration, mostly on the affected hemisphere. SEP changes following thalamic and cortical lesions have been demonstrated in several studies.…”
mentioning
confidence: 98%